The issue of voluntary execution of judgments - Коніжай, Роман Омельянович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
As a part of Problem for voluntary execution of court decisions are considered dates and reasons.Attention is focuses on the need to take into account certain provisions relating to the calculation of the termvoluntary compliance and individual circumstances that it is renewed. Definition the order and proceduresare considered necessity for voluntary execution of court decisions.